2006
DOI: 10.1007/s10461-006-9170-y
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Voluntary HIV Counseling and Testing (VCT), Sexual Risk Behavior and HIV Incidence in Rakai, Uganda

Abstract: We examined the effects of repeat Voluntary HIV counseling and testing (VCT) on sexual risk behaviors and HIV incidence in 6,377 initially HIV-negative subjects enrolled in a prospective STD control for HIV prevention trial in rural Rakai district, southwestern Uganda. Sixty-four percent accepted VCT, and of these, 62.2% were first time acceptors while 37.8% were repeat acceptors. Consistent condom use was 5.8% in repeat acceptors, 6.1% in first time acceptors and 5.1% in non-acceptors. A higher proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 25 publications
2
40
1
Order By: Relevance
“…Given the relatively short period of time VCT has been accessible to Ethiopians, this is a considerable proportion of the client base, comparable to the 38% found in the aforementioned Uganda study [12]. Repeat HIV testing was associated with more reported risk behavior, which is in accordance with findings from other studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Given the relatively short period of time VCT has been accessible to Ethiopians, this is a considerable proportion of the client base, comparable to the 38% found in the aforementioned Uganda study [12]. Repeat HIV testing was associated with more reported risk behavior, which is in accordance with findings from other studies.…”
Section: Discussionsupporting
confidence: 88%
“…Conducted in Rakai, Uganda, this study found 38% repeat testing among acceptors of HIV counseling and testing and higher sexual risk among repeat compared to first-time testers [12].…”
Section: Introductionmentioning
confidence: 80%
“…7 This effect is not so clear in seronegative individuals 8 or in those who have been tested several times. 9 A number of evaluations has been published on the efficacy of interventions to prevent sexual risk behavior and sexually transmitted diseases (STD) in different populations 10 -14 ; however, few studies have evaluated health interventions that focus on reducing risk practices in serodiscordant couples in developed countries, 6,15,16 and practically none of them refer to the era of highly effective antiretroviral treatments (HAART).…”
mentioning
confidence: 99%
“…We have not examined the impact on those that tested HIV negative. A meta-analysis (Weinhardt, Carey, Johnson, & Bickham, 1999) and, more recently, studies from a rural research program in Uganda (Matovu et al, 2005(Matovu et al, , 2007 and from a workplace program in Zimbabwe (Corbett et al, 2007) have cast doubt on the positive effects of VCT on sexual risk behavior among people who are HIV-1 uninfected. Further studies are needed into the impact of VCT on HIV-1 incidence in HIV-negative tested persons (Glick, 2005;Matovu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%